Study on the properties of denitrifying carbon sources from cellulose plants and their nitrogen removal mechanisms. (17th December 2021) - Qi, Liang; Li, Ling; Yin, Lin; Zhang, Wen
Abstract: Carbon sources of cellulose plants are promising materials that enhance the activities of denitrifying bacteria in the groundwater system. To further verify the denitrification performance of cellulose plants and the main factors of affecting the denitrifying system, six cellulose plants from agricultural wastes (wood chip, corn cob, rice husk, corn straw, wheat straw, and sugar cane) were selected for bioavailable organic matter leaching experiments, carbon denitrification experiments, functional bacteria identification, and analysis experiments. The results show that the extracts of cellulose plants contain a mixed carbon sources system including small molecular organic acids, sugars, nitrogen-containing organic components, and esters. The qPCR results showed that the denitrifying bacteria had obvious advantages compared to anaerobic ammonia-oxidizing bacteria during the stable period; the denitrification experiment showed that each of six cellulose plants removed more than 80% of nitrogen, and the denitrification rates reached 1.00–2.00 mg N cm −3 ·d −1 . The supplement of cellulose plants promotes the metabolism rate of denitrifying bacteria, and the additional denitrifying bacteria have little effect on nitrate removal. In summary, the expected denitrification reaction occurred in the cellulose plant system, which is suitable as a carbon source material for water body nitrogen pollution remediation. HIGHLIGHTS: The original matter released from the cellulose plants was efficient for denitrification. The supplemental cellulose plants can intensify the growth of denitrifying bacteria. Adding cellulose plants presented a continuous denitrification process, but the denitrifying rate was slow at the beginning.